Evaluating the efficiency of teaching basic cardiopulmonary resuscitation among medical university students in Ukraine - H.Yu. Tsymbaliuk; A.M. Chervatiuk; V.O. Krylyuk (Медицина неотложных состояний)
Background. Emergency medical care embodies the essence of modern medicine, where basic cardiopulmonary resuscitation (BCPR) has a leading role among the skills required for every medical professional. The ability to quickly and effectively respond to sudden cardiac arrest is considered vital, and thus, the integration of BCPR into the educational process of medical universities in Ukraine indicates the necessity for multidimensional analysis and coordination of teaching methods. Simultaneously, competency in BCPR serves as a litmus test for assessing the effectiveness of future physicians. The meticulous honing of these critical skills forms the basis for the preparedness of the medical field to emergencies, particularly the provision of immediate assistance during sudden cardiac arrests. Objective: to analyze the quality of the educational process in the context of assessing the training of the first-year medical university students in Ukraine on BCPR and level of their theoretical knowledge and readiness to apply it in real clinical situations. Materials and methods. A survey of 1239 third-year students from 13 medical universities in Ukraine, subordinated to the Ministry of Health of Ukraine, was conducted to collect data on their satisfaction with the educational process and confidence in preparedness to perform BCPR. Structured testing was also conducted to assess the level of theoretical knowledge of the adult BCPR algorithm. Results. In the sample studied, most students had BCPR training for the first time in the second year, while 11.7 % had not such training by the time of testing (third year). Students underwent BCPR training as part of various subjects, indicating the absence of a unified program across universities. This lack of standardization may not directly affect the quality of education, but it may imply the need for a more coordinated approach. Additionally, students noted significant disparities in the duration of time for learning BCPR, suggesting a lack of structure in teaching methodologies. Only 37.6 % of respondents rated the training as uniform across different departments, indicating some inconsistency in the educational process, even within the same higher education institution. Positive aspects include 59.7 % of students rating their level of theoretical preparation as high, while 49.8 % rated their practical preparation as high as well. Conversely, 15.6 % gave a strongly negative assessment of practical training, indicating disparities in teaching even within the same educational institution. The results demonstrate that only 48.4 % of respondents positively evaluated overall BCPR education, and only 39.1 % believed they were ready to perform resuscitation in a real situation. Interestingly, a negative correlation was found between the level of theoretical knowledge of BCPR and readiness to perform it in real conditions, which may be explained by the stress and uncertainty during emergencies. This highlights the importance of training in conditions closely resembling real-life scenarios and psychological preparation. Most students emphasize that there is not enough time for practical skills. Despite the fact that 94.8 % of students support the need for simulation training, only half of respondents rated the quality of training in simulation centers as high. Conclusion. The data obtained underscore the need for standardization of BCPR training and changes in approaches to practical training, as well as the importance of using simulation methods in the educational program. It is shown that to improve the quality of education and the confidence of students in their actions in future professional activities, it is critically necessary to add more simulation technologies and psychological preparation to avoid stress when providing assistance in real-life BCPR situations.